2014
DOI: 10.1016/j.colsurfa.2013.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of antimicrobial silver nanoparticles capped with l-cysteine

Abstract: The number of medical applications of silver nanoparticles is constantly expanding due to their high bactericidal properties coupled with low toxicity towards mammalian cells. Because of this expanding use of silver nanoparticles, novel methods of synthesis have been developed in order to achieve nanoparticles preparation through inexpensive and environmentally friendly processes; biogenic synthesis of silver nanoparticles is an approach that meets those requirements.In this work, E. coli cultures centrigugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 54 publications
2
46
1
Order By: Relevance
“…The asymmetric stretching of N-O is found at around 1509 cm À1 . The band centered at 2360 cm À1 might be due to the presence of Ag-S bonds of formed Ag 2 S. The values of stretching frequencies obtained from the IR analysis are in good agreement with the previous reports by Pernia et al [5] and also with the standard literature values. Pernia et al have found almost similar peak around 2300 cm À1 , confirming the formation of cysteine assisted silver sulphide nanoparticles.…”
Section: Topographysupporting
confidence: 90%
See 2 more Smart Citations
“…The asymmetric stretching of N-O is found at around 1509 cm À1 . The band centered at 2360 cm À1 might be due to the presence of Ag-S bonds of formed Ag 2 S. The values of stretching frequencies obtained from the IR analysis are in good agreement with the previous reports by Pernia et al [5] and also with the standard literature values. Pernia et al have found almost similar peak around 2300 cm À1 , confirming the formation of cysteine assisted silver sulphide nanoparticles.…”
Section: Topographysupporting
confidence: 90%
“…Among different techniques of silver sulphide NP preparation [1][2][3][4][5][6] like, chemical bath deposition, spray pyrolysis, successive ionic layer absorbance and reaction, thermal evaporation, sol-gel reduction, chemical deposition; we have opted an in situ chemical reduction pathway due to its low cost, easily controllable and large scale production facilities. Depending upon the preparation technique, silver sulphide nanoparticles can show different shapes and sizes, which lead to diversified optical and electronic/electrical properties [1][2][3][4][5][6]. Making a complex of the precursor metal ion (here Ag + ) by a large organic molecule may result in some specific shape of the product semiconductor, as such large molecules can also act as the structure orienting or caging agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this peak affirmed the fact that the SNPs were capped by L-cysteine present in the leaf extract. The phenomenon of capping action by L-cysteine and the stability was explained by Perni et al (2014) for the SNP synthesis using E. coli. This is further supported by the finding of Mishra and Sardar, 2012, who concluded that the free thiol groups present in the proteins were responsible for the reduction of silver nitrate to silver nanoparticle formation.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…These methods include the intracellular or extracellular production of nanoparticles of different elements, mainly metals, oxides or sulphides and noble metal alloys by a variety of microorganisms [7] and plants extracts [6]. Also mixed methods using microorganisms and other added biocompatible materials have been reported [9]. An invertebrate's extract has also been used recently for silver and gold nanoparticles synthesis [10].…”
Section: Introductionmentioning
confidence: 99%